Réponses

Meilleure réponse !
2012-11-27T19:05:34+01:00

D= 2x(7-5)+4(2x²-1)

D=2x fois 7 + 2x fois 5 + 4 fois 2x² + 4 fois (-1)

D= 14x + 10x + 8x² -4

D 8x² + 24x - 4

 

x = -1

D= 2 fois (-1)(7-5) + 4 ( 2 fois (-1) -1)

D = -2 (7-5)+4(-2-1)

D= -2 fois 7 -2 fois 5 + 4fois (-2) + 4 fois (-1)

D = -14 - 10 - 8 - 4

D = 36

 

Voilà, j'espère que je t'ai aidé =)

2012-11-27T19:07:26+01:00

D=2x(7-5x)+4(2x²-1)

D=14x-10x²+8x²-4

D=2x²+14x-4

 

Lorsque x vaut -1

 

D(-1)= 2*(-1)²+14*(-1)-4

D(-1)=2*1+14-4

D(-1)=2+14-4

D(-1)=12